EDUCATING STUDENTS IN THE NATIONAL SPIRIT THROUGH MUSIC IS AN IMPORTANT PEDAGOGICAL PROBLEM - Yoʻldosheva Parvina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The spiritual heritage, cultural values, historical monuments of the zone are one of the most important factors in the formation of spirituality.